Beyond Impunity: Reconstructing Criminal Accountability for Torture by Law Enforcement Officials - Suhendar, Suhendar; Permana, Virgiawan Cikal; Putra, Rengga Kusuma (Fakultas Hukum Universitas Islam Jakarta, 2025)
Torture perpetrated by law enforcement officials continues to occur within Indonesia’s criminal justice system despite explicit constitutional prohibitions and binding international human rights commitments. This persistence indicates deficiencies in the framework of criminal accountability and contributes to entrenched patterns of impunity. This study examines the normative and structural obstacles to prosecuting torture and reconstructs a more effective model of criminal accountability. Employing a normative legal method with statutory and conceptual approaches, the research analyzes constitutional provisions, national legislation, and relevant doctrinal sources. The findings reveal that ambiguous regulatory formulations, the predominance of an individualistic paradigm in criminal law, the absence of a specific and autonomous offence of torture, and the lack of structural accountability mechanisms collectively weaken enforcement. Moreover, existing legal frameworks insufficiently address command responsibility and institutional dimensions of abuse, thereby reinforcing systemic impunity. The study concludes that criminal law reform should incorporate explicit recognition of torture as a distinct offence, expand accountability within hierarchical command structures, and strengthen independent oversight and victim protection mechanisms. Harmonization with international standards and the establishment of effective enforcement mechanisms are recommended to ensure consistent and transparent prosecution of torture cases.